Islam and Tolerance Education for the Sustainable Development Goals (SDGs) - Abdullah Mahmud; Zamroni; Hamim Ilyas (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to explore the integration of Islamic teachings on tolerance and multicultural education within the framework of the Sustainable Development Goals (SDGs). The focus is on analyzing the values of democracy, tolerance, and multiculturalism derived from the Qur'an and Islamic education, emphasizing their relevance in promoting global peace and inclusivity. The study is motivated by fundamental Islamic principles, including prohibitions against denouncing other religions, respect for human dignity regardless of belief, interfaith communication, freedom of religion, the prohibition of forced adherence to any religion, maintaining positive assumptions (husnudzan) about others, and acknowledgment of diverse religious practices. Theoretical framework: The theoretical framework is grounded in the intersection of Islamic ethics and the SDGs, particularly Goal 4 (Quality Education), Goal 16 (Peace, Justice, and Strong Institutions), and Goal 17 (Partnerships for the Goals). Literature Review: The literature review highlights previous studies on tolerance in Islamic teachings and their implementation in educational settings, showcasing how Islamic education aligns with global goals. Methods: This research adopts a qualitative field study approach, collecting data through in-depth observations and interviews with educators and students at the University of Muhammadiyah Surakarta. Results: The findings reveal that democratic and tolerant multicultural values in Islamic education are implemented through three learning models: (1) Baitul Arqam for Muslim students during semesters 1-2, (2) Classical Learning for non-Muslim students in semesters 1-2, and (3) Integrated Classical Learning for both Muslim and non-Muslim students in semesters 3-4. The study demonstrates that these models effectively foster a culture of inclusivity and tolerance among students from diverse backgrounds. Implications: The findings have significant implications for developing educational frameworks that contribute to SDG targets by promoting peaceful coexistence and mutual respect. Novelty: The novelty of this research lies in linking Islamic educational practices with the SDGs, offering a unique perspective on the role of religious education in achieving global sustainability.